Schizosthetus Athias-Henriot, 1982 (Mesostigmata: Parasitidae): the description of a new species from China - Zhang, Shuo; Xie, Lixia; Wang, Haoran; Dong, Minghang; Yan, Yi (Zootaxa, 2024)
A new species, Schizosthetus baixuelii sp. nov., is described based on females from Ningxia Hui Autonomous Region, China. A key to the known species of the genus is presented.